Control System Analysis and Design of Quadcopter in the Presence of Unmodelled Dynamics and Disturbances. Issue 2 (2020) - Ali, Muhammad Z.; Ahmed, Aftab; Afridi, Hamad K.
Abstract: UAVs especially quadcopters have recently caught the attention of researchers and manufacturers due to their various commercial and military applications like surveillance, photography and many others. They have small sizes since have low cost, easy manufacturing, extreme maneuverability and VTOL capabilities. This paper addresses the problem of unmod-elled dynamics and disturbances while designing an appropriate control law for the quadcopter UAV having very coupled nonlinear dynamics. Most of the controllers available in the literature ignore Coriolis terms in the model and small signal approximations are made to linearize or simplify the model about certain operating conditions. But such control system has a very limited performance and fails to deliver the desired results even for small disturbances and parametric variations since the assumptions no longer remain valid. We have derived an extensive nonlinear model of quadcopter with least approximations in terms of linear velocities in body frame, position in the inertial frame, the Euler angles and their rates. We have designed a feedback linearization based nonlinear controller using a novel approach. This has further been cascaded with sliding mode control and backstepping based control to handle uncertainties. The simulation results of this controller have also been included for a known quadcopter model.